Application of Constructive Systems of Living Nature in Furniture Design (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article discusses different types of structural systems, such as mesh, lattice and ribbed systems. Changing the shape of natural structure in the form of lattice, mesh and ribbed systems and how they influence lighting fixtures design. Examples of various types of structural systems in nature and in lighting fixtures are given.